Attitudes of physicians towards target groups and content of the discharge summary: a cross-sectional analysis in Styria, Austria. Issue 12 (17th December 2019) - Hoffmann, Magdalena; Schwarz, Christine Maria; Pregartner, Gudrun; Weinrauch, Maximilian; Jantscher, Lydia; Kamolz, Lars; Brunner, Gernot; Sendlhofer, Gerald
Abstract : Objectives: The discharge summary (DS) represents one of the most important instruments to ensure a safe patient discharge from the hospital. They sometimes have poor quality in content and often include medical jargon, which the patient and their relatives cannot easily understand. Therefore, many risks for patient safety exist. This study investigated the questions for whom the DS is and which contents are necessary to ensure a safe treatment. Design: Cross-sectional analysis. Setting: Styria, Austria. Participants: 3948 internal and external physicians were consulted. Interventions: An online survey consisting of 24 questions was conducted. The survey was distributed to physicians working in the province of Styria, Austria, in 2018 over a period of 6 months. Main outcomes and measures: Attitudes of internal and external physicians in terms of target group, content and health literacy. Results: In total, 1060 physicians participated in the survey. The DS is considered as a communication tool among physicians (97.9%) and the patients are also indicated as addressees (73.5%). Furthermore, there is a high level of agreement that understandable information in the DS leads to fewer questions of the patients (67.9%). Conclusion: In conclusion, the DS is not only seen as a document for the further treating physician but is also relevant for the patient. Incorporating the patient into their treatment at all levels may possibly strengthen the individual health literacy of the patient and their caring relatives.